2021
DOI: 10.1002/pc.26060
|View full text |Cite
|
Sign up to set email alerts
|

Role of nano‐zirconia in the mechanical properties improvement of resin cement used for tooth fragment reattachment

Abstract: Dental fractures of the anterior teeth are a common form of dental trauma. Reattachment of fractured tooth fragment by means of self‐adhesive resin cement is currently compromised by the poor mechanical properties of these ceramics. Herein, we synthesized zirconium dioxide nanoparticles (nano‐ZrO2) using the Co‐precipitation approach and then mixing it in different concentrations (1.0, 2.0, 3.0, and 5.0 wt%) with the commercially available RelyX™ Unicem self‐adhesive universal resin cement (ARC) forming, nano‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Figure 2 presents the FTIR spectra of the coupling agent MTS, raw ZrO 2 , and mercapto‐functionalized ZrO 2 (SH‐ZrO 2 NPs), offering visual representation of the spectroscopic results. In the spectrum of raw ZrO 2 , a strong and broad band at 3441 cm −1 , accompanied by a broad peak near 1630 cm −1 , indicates the presence of physisorbed and possibly coordinated water, with the latter being attributed to the bending mode (δ HOH ) of coordinated molecular water 51 . The detection of a peak at 1406 cm −1 provides evidence for the existence of ZrOH groups, characterized by their distinctive bending vibration 52 .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Figure 2 presents the FTIR spectra of the coupling agent MTS, raw ZrO 2 , and mercapto‐functionalized ZrO 2 (SH‐ZrO 2 NPs), offering visual representation of the spectroscopic results. In the spectrum of raw ZrO 2 , a strong and broad band at 3441 cm −1 , accompanied by a broad peak near 1630 cm −1 , indicates the presence of physisorbed and possibly coordinated water, with the latter being attributed to the bending mode (δ HOH ) of coordinated molecular water 51 . The detection of a peak at 1406 cm −1 provides evidence for the existence of ZrOH groups, characterized by their distinctive bending vibration 52 .…”
Section: Resultsmentioning
confidence: 98%
“…In the spectrum of raw ZrO 2 , a strong and broad band at 3441 cm À1 , accompanied by a broad peak near 1630 cm À1 , indicates the presence of physisorbed and possibly coordinated water, with the latter being attributed to the bending mode (δ HOH ) of coordinated molecular water. 51 The detection of a peak at 1406 cm À1 provides evidence for the existence of Zr OH groups, characterized by their distinctive bending vibration. 52 Moreover, the chemical structure of the nanoparticles is defined by the presence of Zr O bonds, identifiable at wavenumbers of 540 and 747 cm À1 .…”
Section: Resultsmentioning
confidence: 99%
“…Afterward, 70 μL of SRB solution (0.4% w/v) was mixed and left at RT for 10 min in the dark. Plates were cleaned 3 times with 1% acetic acid and air-dried for 24 h. The protein-bound (SRB) stain was then solubilized in 150 μL of TRIS (10 mM), and the optical density was recorded at 540 nm via (the BMG LABTECH-FLUO star Omega microplate reader, Ortenberg, Germany). , …”
Section: Methodsmentioning
confidence: 99%
“…While, incorporation of nano‐SiO 2 into cementitious composites has been shown to increase the materials' resistance to chloride penetration, freezing and thawing, permeability, corrosion resistance, and fire resistance 47,48 . When nano‐ZrO 2 by 3.0 wt% is used as a filler in cementitious materials, the mechanical properties of concrete can be increased 49 . It has been shown that incorporation of nano‐Al 2 O 3 at 5% results in an growth in modulus of elasticity of 143% 50 .…”
Section: Introductionmentioning
confidence: 99%
“…47,48 When nano-ZrO 2 by 3.0 wt% is used as a filler in cementitious materials, the mechanical properties of concrete can be increased. 49 It has been shown that incorporation of nano-Al 2 O 3 at 5% results in an growth in modulus of elasticity of 143%. 50 When 5% nano-Fe 2 O 3 is added to cement composites, the electrical resistivity of these materials can be reduced by 45%.…”
mentioning
confidence: 99%